Case Report: Subtotal Lymphoid and Total Marrow Irradiation as Bridge Therapy to CD19-Directed CAR T Cells in a Chemorefractory DLBCL With Leukemic Involvement - Saldi, Simonetta; Perriello, Vincenzo Maria; Falini, Lorenza; Ruggeri, Loredana; Fulcheri, Christian; Ciardelli, Sara; Innocente, Alessandra; Ballanti, Stelvio; Baffa, Nicodemo; Flenghi, Leonardo; Pierini, Antonio; Aristei, Cynthia; et al. (Frontiers in Immunology, 2022)
CAR T cell therapy has transformed the salvage approach for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). Maintaining disease control before CAR T cell infusion during product manufacturing (so-called bridging therapy) is an important step to optimizing outcome. Among possible bridging therapies, radiation therapy (RT) represents a valuable option, particularly when the disease is limited. Here, we report for the first time on a patient with chemorefractory-transformed DLBCL showing nodal, extranodal, and massive bone marrow (BM) lymphoma infiltration associated with leukemic involvement, a successful bridge therapy to CD19-directed CAR T cell therapy by subtotal lymphoid/total marrow irradiation plus thiothepa followed by reinfusion of CD34+ autologous hematopoietic stem cells. Such a novel bridging regimen allowed a significant reduction of nodal and BM tumor volume while improving blood cell count before CAR T cell infusion. The PET-CT scan and BM evaluation performed at 1, 3, and 6 months after treatment showed complete remission of the disease. A relapse occurred at almost 1 year in lymph nodes because of CD19 antigen escape while the BM remained free of disease. This extended radiotherapy approach may be an effective bridging therapy for chemorefractory DLBCL patients eligible for CAR T cells who present with a high tumor burden, including massive BM involvement associated with leukemic involvement. This preliminary evidence is worth confirming in additional patients.